1989
DOI: 10.1007/bf01975164
|View full text |Cite
|
Sign up to set email alerts
|

Antibody specificity for human immunodeficiency virus type 1 in serum and cerebrospinal fluid from patients with AIDS and AIDS-related complex

Abstract: Since little information has been reported about the specificity of antibodies to human immunodeficiency virus type 1 (HIV-1) found in the cerebrospinal fluid (CSF), 21 CSF and serum specimens were examined from 19 patients with clinical AIDS, AIDS-related complex, or asymptomatic HIV-1 infection. The predominant specificity of antibodies using Western blot analysis in both serum (100%) and CSF (100%) was directed toward env gene products. The next most common antibody specificities were to the pol gene produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Some analyses, however, demonstrated that antibodies directed towards several HIV proteins and of different isotypes and IgG subclasses can also be found in body fluids, such as cerebrospinal fluids, saliva and genital secretions ( table 3 ) [49,[63][64][65][66][67][68][69][70][71] . Further studies are still necessary to clarify to what extent antibodies found at these sites represent a transudate from the blood or are locally produced, and to elucidate their protective role during HIV infections [49,63,64,66,[70][71][72][73][74][75][76][77] .…”
Section: Analysis Of Isotypes Functions and Specificities Of Hiv-spementioning
confidence: 99%
“…Some analyses, however, demonstrated that antibodies directed towards several HIV proteins and of different isotypes and IgG subclasses can also be found in body fluids, such as cerebrospinal fluids, saliva and genital secretions ( table 3 ) [49,[63][64][65][66][67][68][69][70][71] . Further studies are still necessary to clarify to what extent antibodies found at these sites represent a transudate from the blood or are locally produced, and to elucidate their protective role during HIV infections [49,63,64,66,[70][71][72][73][74][75][76][77] .…”
Section: Analysis Of Isotypes Functions and Specificities Of Hiv-spementioning
confidence: 99%